Acoustic estimation of seafloor parameters: a Radial Basis Functions approach - Caiti, A. (1996)
A novel approach to the estimation of seafloor geoacoustic parameters from the measurement of the acoustic field in the water column is introduced. The approach is based on the idea of approximating the inverse function that links the geoacoustic parameters with the measured field through a series expansion of radial basis functions. In particular, Gaussian basis functions are used in order to ensure continuity and smoothness of the approximated inverse. The main advantage of the proposed approach relies on the fact that the series expansion can be computed off-line from simulated data as soon as the experimental configuration is known. Data inversion can then be performed in true real time as soon as the data are acquired. Simulation results are presented in order to show the advantages and limitations of the method. Finally, some inversion results from horizontal towed array data are reported, and are compared with independent estimates of geoacoustic bottom properties.